The effects of pulsed magnetic field exposure on the permeability of leukemia cancer cells. (June 2014) - Shankayi, Zeinab; Firoozabadi, S. Mohammad P.; Mansourian, Mahsa; Mahna, Akram
Abstract Purpose: The newer methods of cancer treatment require new idea of drug delivery in cancer cells. Due to numerous researches electromagnetic field affect on cell function and cell membrane for possible therapeutic and drug delivery. In this article, we determined in vitro uptake of fluorescent dyes into the attached K562 cells due to time-varying magnetic field exposure. Method and material: The K562 cells were exposed to magnetic pulses via Magstim stimulator and double 70 mm coil. The strength and duration of pulses in all experiments were the same and three different frequencies of 0.25, 1 and 10 Hz pulses for 56, 112 and 28 numbers of pulses were applied (nine experimental groups) and uptake of Ly and PI was measured in each group. Result: Our results show that magnetic field can efficiently increase permeability. Among the treatment groups, the system gives the optimal permeabilization when cells are exposed to a train of 28 pulses with 1 Hz frequency.